Open Educational Resources and Student Course Outcomes: A Multilevel Analysis - Winitzky-Stephens, Jessie R; Pickavance, Jason (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
Salt Lake Community College (SLCC) is Utah’s largest open enrollment college, and as an institution, is concerned about the expense associated with attaining a degree. All students face challenges in paying for their education, but SLCC students tend to have fewer resources to dedicate to school than students at other institutions in the state. While faculty and administrators have little control over the rising cost of tuition, they are able to offer students open educational resources (OER) to cut down on textbook costs. Salt Lake Community College’s OER initiative was implemented in Summer 2014, and has since expanded to include 125 sections in Spring 2016. We examine OER’s impact on three measures of student success: course grade, likelihood of passing, and likelihood of withdrawing. We use a multilevel modeling (MLM) approach in order to control for student, instructor, and course effects, and found no difference between courses using OER and traditional textbooks for continuing students. For new students, there is evidence that OER increases average grade. However, student-level differences such as demographic background and educational experience have a far greater impact on course grade and likelihood of passing or withdrawing than an instructor’s use of an OER text. Future research should focus on longer-term impacts of OER on retention, completion, and transfer.